Penguatan Kelompok Sadar Wisata Penguatan Kelompok Sadar Wisata Penguatan Kelompok Sadar Wisata - Lasti Nur Satiani (Jurnal Abdimas Pariwisata, 2020)
Strengthening Tourism Awareness Group in Rural Areas through Tourism Destination Management Training. Tourism is a strategic sector that makes a very important contribution. Tourism villages / rural areas are one of the most developed tours. A tourist village is one way for the welfare of the village community. Tourism is expected to be managed by the community itself and of course, the results can be enjoyed by local communities. The City of Salatiga Tourism Office collaborates with the Satya Wacana Christian University Tourism Destination Study Program to hold governance training for the Salatiga community in priority rural tourism development areas. The community needs to be equipped with sufficient destination management so that they are able to manage and develop destinations in their respective regions. Therefore, this community service activity is carried out in the hope that it can facilitate local people to have knowledge about tourism management. The success of this training activity will be perfect if it is accompanied by direct mentoring activities when the community starts planning tourism.